ANALISA VALUE CREATION PADA PERGURUAN TINGGI SWASTA DI SURABAYA BERDASARKAN PERSEPSI MAHASISWA JURUSAN INFORMATIKA - Elsa Sandra (Business Accounting Review, 2013)
In order to survive in the competition, The Private Universities in Surabaya especially those with the highest tuition must actively seek ways to create value. Value can occur in universities that can provide benefits, both service quality and images that exceed the cost of tuition on offer. This study aimed to determine whether there were differences in value creation in Private Universities based on the perception of the students of informatics department. The data were collected by distributing questionnaires to students majoring in informatics in five private universities with the highest tuition fees in Surabaya. To avoid any misinterpretation of the data obtained in the research process, there were several steps that must be passed as to test the validity, reliability and One-Way ANOVA by SPSS. The results of the study, showed that there was no difference in universities’ value creation based on sex. However it was found that there were significant differences in value creation based on the student’s GPA and seniority.